Simultaneous Spectrophotoetric Estimation of Bromhexine Hydrochloride and Pseudoephedrine Hydrochloride in Tablet Dosages - Gupta, V.; Verma, M.; Misra, U.; Nema, R.K. (Asian Journal of Chemistry, 2010)
Two simple, precise and economical derivative spectrophotometric methods have been developed for the simultaneous determintion of bromehexine hydrochloride and pseudoephedrine hydrochloride in tablet formulations. In zero order, bromhexine hydrochloride and pseudoephedrine hydrochloride shows absorption maxima of 308 and 257 nm respectively in both methanol and distilled water. Beer's law is obeyed in the concentratrion range of 10-60 μg/mL for bromhexine hydrochloride and 75-900 μg/mL for pseudoephedrine hydrochloride at the selected wavelengths. The results of analysis validated statistically and by recovery studies.